Letters - Brown, Itshaq H. (Refuge: Canada’s Journal on Refugees, 1983)
Your "Newsflash" in the September/ October issue of " Refuge " stated: ’The UNHCR has cancelled its agreement of co-operation with the Canadian Founda- tion for Refugees".